Pengaruh Penggunaan Media Infomasi dan Budaya Religius Terhadap Akhlak Siswa SD Negeri Menang - Ridwan Ardianto; Retno Widyaningrum (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research is a descriptive quantitative research, in this research the researcher uses three variables, namely the use of information media (X1), religious culture (X2) and student morals (Y). This research was carried out by distributing questionnaires to SDN MENANG students. The subjects in this research were all 25 students at SDN MENANG. The validity of the data uses the method triangulation technique, the analysis uses descriptive statistical analysis SPSS Persian 34. The results of the research show that there is a significant influence between the influence of religious culture on student morals at SDN MENANG, namely in accordance with the coefficient of determination test (R2) of the influence of the use of information media and religious culture on morals. 4% of students use Information Media and 2% for Religious Culture, while the rest is influenced by other variables.